2007
DOI: 10.1093/carcin/bgm008
|View full text |Cite
|
Sign up to set email alerts
|

Persistent activation of Rac1 in squamous carcinomas of the head and neck: evidence for an EGFR/Vav2 signaling axis involved in cell invasion

Abstract: The poor prognosis associated with head and neck squamous cell carcinoma (HNSCC) is primarily due to both local invasion and the regional and/or distant metastatic spread. Recent findings have provided evidence that the acquisition of a motile and invasive phenotype by cancer cells involves the dysregulated function of key intracellular molecular mechanisms together with aberrant signaling events initiated by the surrounding microenvironment. These intrinsic and extrinsic biochemical pathways in turn often con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 36 publications
5
65
0
1
Order By: Relevance
“…This assumes the measured decrease in active RhoA (cf. 27 ± 12 %, Figure 6) is comparable for the other Rho-GTPase proteins present in this cell 38 . The absence of the mechanosensitive response in Toxin Btreated cells leads us to suggest that the linkages are different than present in the untreated cells.…”
Section: Membrane-cytoskeleton Bonds Depend Upon F-actin Integrity Ansupporting
confidence: 64%
See 1 more Smart Citation
“…This assumes the measured decrease in active RhoA (cf. 27 ± 12 %, Figure 6) is comparable for the other Rho-GTPase proteins present in this cell 38 . The absence of the mechanosensitive response in Toxin Btreated cells leads us to suggest that the linkages are different than present in the untreated cells.…”
Section: Membrane-cytoskeleton Bonds Depend Upon F-actin Integrity Ansupporting
confidence: 64%
“…and an H-ras mutation 38 that results in persistently-active Rho-GTPases. We apply a constant loading rate to rupture the bonds and detect a biphasic time-loading rate relationship.…”
mentioning
confidence: 99%
“…In this study, PC-9 cells showed actin-rich lamellipodia at both ends of their long axis. This suggests enhanced activation of Rac1, probably because of activation of the EGFR-Ras axis by mutation of EGFR [31]. In fact, inhibition of EGFR resulted in disappearance of lamellipodia and decrease of motile activity, while formation of filopodia was observed.…”
Section: Discussionmentioning
confidence: 95%
“…48,55,[90][91][92][93][94] A number of HNSCC cell lines have constitutively high levels of Rac1 activity, and inhibition of Rac activity results in reduced invasion capability. 95 In most cases, the increased Rac1 activity correlated with increased tyrosine phosphorylation of the Rac GEF Vav2 induced by EGFR, but an alternative pathway used Ras activation. The role of the Janus kinase (JAK)-signal transducer and activator of transcription (STAT) pathway in HNSCC invasion is complex.…”
Section: Cell Surface Receptors Influence Invasivementioning
confidence: 96%